Investments on urban land valuation by real options – The Portuguese case. (August 2021) - Couto, Gualter; Martins, Dulce; Pimentel, Pedro; Castanho, Rui Alexandre
Abstract: This study aims to evaluate unexploited urban land in Portugal, for the construction of new apartments, with the real options analysis's contribution, using the Quigg model, adapted to the reality of the Portuguese market. This work defines a value associated with the land, referring to the construction option. This option gives the right, but not the obligation, to build the project at any time. Therefore, the new land value is maximized in the optimal timing to define the best moment to carry out the investment. The study shows that in the Portuguese case, when the time horizon changes from 5 to 10 years, both the value of the deferral options and the global value of the land increase considerably, exposing the deferral options' sensitivity to the time horizon variable in the process of evaluation. Besides, considering the land evaluation process in Portugal, it is possible to conclude that, on average, the deferral option represents 9, 09% of the land's final value, varying between 1, 40% and 20, 10%. The decision to defer the construction of the investment project adds value to the undeveloped land and should be considered in the investment decision-making process. Highlights: This study aims to evaluate unexploited urban land in Portugal, with the real options analysis. This work has a high concern for companies promoting real estate projects, which can take advantage of a new analysis tool. This new method of evaluation of investment projects is very important on real assets. The flexibility and uncertainty in future decision-making moments alters the entire structure of expected cash flows.